A Surface-Active Pt(II) Bis-N-Heterocyclic Carbene (NHC) Complex for Interface-Enhanced Supported Ionic Liquid Phase (SILP) Catalysis - Bergen, Alexander; Hemmeter, Daniel; Barreto, Jade; Maier, Florian; Scheurer, Andreas; Heinemann, Frank Wilhelm; Steinrück, Hans-Peter; Meyer, Karsten (Chemistry - A European Journal, 2025)
We present the preparation and investigation of a fluorine-free surface-active bis-N-heterocyclic carbene (NHC) platinum(II) complex — trans-[Pt(mPEG3C8Im)2Cl2] — for interface-enhanced supported ionic liquid phase (SILP) catalysis within a group of (mPEGn)-substituted ionic liquids (ILs) ([(mPEGn)2Im][A] ILs). The complex was characterized by means of single-crystal X-ray diffraction (scXRD) analysis and multinuclear (1H, 13C, 195Pt) NMR spectroscopy, indicating the presence of two almost equimolar syn–anti-rotamers of the square-planar complex in solution. Angle-resolved X-ray photoelectron spectroscopy (ARXPS) revealed pronounced interface-accumulation of trans-[Pt(mPEG3C8Im)2Cl2] in IL solutions of [(mPEG2)2Im][A] (A−=I− and PF6−).
CRIS-Team Scopus Importer:2025-01-31
Keywords: Interfaces; Ionic liquids; Platinum N-heterocyclic carbene complexes; X-ray photoelectron spectroscopy

Correlation of Macroscopic Surface Tension and Microscopic Surface Composition of Binary Ionic Liquid Mixtures with Common Cations and Anions of Different Size - Zhai, Ziwen; Barreto, Jade; Hemmeter, Daniel; Maier, Florian; Steinrück, Hans-Peter; Koller, Thomas Manfred (Journal of Physical Chemistry B, 2025)

Surface Chemistry of a [C2C1Im][OTf] (Sub)Wetting Layer on Pt(111): A Combined XPS, IRAS, and STM Study - Bühlmeyer, Hanna; Talwar, Timo; Eschenbacher, Roman; Barreto, Jade; Hauner, Jonas; Knörr, Lukas; Steinrück, Hans-Peter; Maier, Florian; Libuda, Jörg (ACS Applied Materials and Interfaces, 2024)
The concept of a solid catalyst with an ionic liquid layer (SCILL) is a promising approach to improve the selectivity of noble metal catalysts in heterogeneous reactions. In order to understand the origins of this selectivity control, we investigated the growth and thermal stability of ultrathin 1-ethyl-3-methylimidazolium trifluormethanesulfonate [C2C1Im][OTf] films on Pt(111) by infrared reflection absorption spectroscopy (IRAS) and X-ray photoelectron spectroscopy (XPS) in time-resolved and temperature-programmed experiments. We combined these spectroscopy experiments with scanning tunneling microscopy (STM) to obtain detailed insights into the orientation and adsorption geometry of the ions in the first IL layer. Furthermore, we propose a mechanism for the thermal evolution of [C2C1Im][OTf] on Pt(111). We observe an intact IL layer on the surface at temperatures below 200 K. Adsorbed [C2C1Im][OTf] forms islands, which are evenly distributed over the surface. The [OTf]− anion adsorbs via the SO3 group, with the molecular axis perpendicular to the surface. Anions and cations are arranged next to each other, alternating on the Pt(111) surface. Upon heating to 250 K, we observe changes in geometry and structural distribution. Whereas at low temperature, the ions are arranged alternately for electrostatic reasons, this driving force is no longer decisive at 250 K. Here, a phase separation of two different species is discernible in STM. We propose that this effect is due to a surface reaction, which changes the charge of the adsorbates. We assume that the IL starts to decompose at around 250 K, and thus, pristine IL and decomposition products coexist on the surface. Also, IRAS and XPS show indication of IL decomposition. Further heating leads to increased IL decomposition. The reaction products associated with the anions are volatile and leave the surface. In contrast, the cation fragments remain on the surface up to temperatures above 420 K.
CRIS-Team Scopus Importer:2024-05-10
Keywords: infrared reflection absorption spectroscopy; ionic liquids; Pt(111); scanning tunneling microscopy; SCILL; X-ray photoelectron spectroscopy

Ultrathin [C1C1Im][Tf2N] Layers on Supported Mn3O4(001) Films - Barreto, Jade; Talwar, Timo; Steinrück, Hans-Peter; Maier, Florian (Topics in Catalysis, 2025)
In the Solid Catalyst with Ionic Liquid Layer concept, activity and selectivity of a solid catalyst such as metal particles supported on porous oxides can be tuned and optimized by ultrathin ionic liquid (IL) coatings. In this context of ILs interacting with oxide surfaces, we report on the adsorption behavior and thermal stability of the IL 1,3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide ([C1C1Im][Tf2N]) on well-ordered Mn3O4(001) thin films grown on Au(111) using angle-resolved X-ray photoelectron spectroscopy. We observe the formation of a two dimensional IL wetting layer for IL coverages ≤ 0.5 ML, while multilayers on top of the closed wetting layer (≥ 0.5 ML) grow in 3D islands. For both coverage regimes, the IL anion is preferentially oriented in a cis conformation with the CF3 groups preferentially pointing to the vacuum and SO2 groups towards the oxide surface. Temperature-programmed XPS shows that the multilayer starts to desorb at around 300 K as neutral ion pairs. Above 400 K, the IL wetting layer decomposes, which is characterized by the disappearance of cation-related XPS signals until 450 K, while anion signals remain until 500 K. In comparison to [C1C1Im][Tf2N] films on reactive metal surfaces such as Cu(111) and Pt(111), the IL exhibits a higher thermal stability on Mn3O4(001).
CRIS-Team Scopus Importer:2025-02-14
Keywords: Angle-resolved X-ray photoelectron spectroscopy (ARXPS); Ionic liquids; Manganese oxide; Mn; [C

Ultrathin Films of a Nitrile-Functionalized Ionic Liquid [C₃CNC₁Im][Tf₂N] on Au(111) and Pt(111): Adsorption, Growth, and Thermal Behavior - Talwar, Timo; Barreto, Jade; Fernandez, Cynthia; Steinrück, Hans-Peter; Maier, Florian (Langmuir, 2024)
We studied the adsorption and thermal behavior of the nitrile-functionalized ionic liquid (IL) [C3CNC1Im][Tf2N] on Au(111) and Pt(111) between 150 and 600 K. Ultrathin films were prepared at 150 K by physical vapor deposition (PVD) and were characterized by angle resolved X-ray photoelectron spectroscopy (ARXPS). At 150 K, the IL adsorbs intact with a similar orientation on both surfaces: In the first layer, the so-called wetting layer, the cation lies flat on the surface and the anion is bound in cis-configuration with the SO2 groups toward the surface and the CF3 groups away from the surface. On Au(111), subsequent deposition of IL in the multilayer regime at 150 K shows 2D growth up until ∼0.75 ML and a transition to moderate 3D at higher coverages. Temperature-programmed XPS indicates a change in surface morphology toward more pronounced 3D islands for the multilayers on top of the wetting layer between 220 and 290 K. From 350 to 440 K, desorption of multilayers occurs, with IL decomposition starting at 375-400 K. On the more reactive Pt(111) surface, decomposition starts already above 280 K. Notably, this temperature is ∼80 K higher than the onset for decomposition of related nonfunctionalized imidazolium-based ILs, that is, [C2C1Im][OTf], [C1C1Im][Tf2N], and [C8C1Im][Tf2N] on Pt(111). This difference is attributed to the nitrile functionality. Our findings demonstrate that functionalizing ILs significantly modifies their thermal properties, which is of high relevance for SCILL (solid catalyst with an ionic liquid layer) systems.
CRIS-Team Scopus Importer:2025-02-04